Implications of sustainable features on life-cycle costs of green buildings - Weerasinghe AS; Ramachandra T (My University)
The green buildings seem unattractive to developers who prioritize fast investment returns, due to costs attributed to implementing sustainable features and consequently, only 19% of existing buildings are certified for green, globally. Furthermore, green buildings are aimed at achieving a minimum sustainability level in certification. Therefore, the current study aims to investigate the significant sustainable features and the implications of those features on green buildings' life-cycle costs. The study involved a preliminary investigation to find the significant sustainable features implemented. Subsequently, two green buildings were carefully selected, and a detailed analysis was performed. The data relating to the green building construction, operation and maintenance costs were collected and analysed using Net Present Value. The features have varying degree of contribution to sustainability in terms of the achievement of allocated points in the rating system. The certified buildings have achieved over 75% of allocated points in terms of water efficiency and sustainable sites features, while the achievement level of other features is below average level. Further, highly achieved features are more economical in terms of their less contribution to construction and maintenance costs. On the other hand, the features with lower achievement in certification, contribute significantly to construction and maintenance costs, while providing higher savings during operation. Therefore, the current study recommends, green building investors to select the most suitable features for a given construction based on their respective contributions to the life-cycle cost of green buildings.
CAUL read and publish agreement 2022